製鋼スラグと木材チップを骨材とするモルタルブロックからの成分溶出 - 藤澤 武蔵; 稲川 有徳; 上原 伸夫 (鉄と鋼, 2025)
Mortar blocks to heal coastal environments were prepared with cement and fine aggregates composed of steel slag and wood chips. Inorganic and organic species leached from the pulverized mortar blocks prepared in this work. Fe, Si, Mg, Al, Mn, Ca, and S were contained in the leachate as inorganic species. Among them, Fe, Si, Mg, Al, and Mn mainly leached from the steel slag in the mortar block. The elution of these elements was facilitated by the wood chips. Because Ca and S mainly leached from the cement component, the ratio of steel slag and wood chips added to the mortar block gave no effects on the elution of these elements. The leachate of the mortar block also contained not only vanillin and benzoic acid derived from lignin, but also sugar derived from cellulose. These organic substances evolved from the wood chips in the mortar blocks during the preparation process. The steel slag added in the mortar blocks facilitated leaching these organic components. Because the organic and inorganic components feed nutrients to aquatic lives in coastal areas, the prepared mortar blocks could recover damaged coastal environments.